Does cognitive frailty predict delayed neurocognitive recovery after noncardiac surgery in frail elderly individuals? Probably not - Zhang, Jingya; Basnet, Diksha; Du, Xue; Yang, Junjun; Liu, Jiehui; Wu, Fan; Zhang, Xiaoqing; Liu, Jianhui (Frontiers in Aging Neuroscience, 2022)
Introduction: Delayed neurocognitive recovery (DNR) is a common post-surgical complication among the elderly. Cognitive frailty (CF) is also an age-related medical syndrome. Whereas, little is known about association between CF and DNR. This study aimed to study weather CF is associated with DNR in elderly patients undergoing elective noncardiac surgery, as well as to explore the potential risk factors for DNR in aging with frailty and construct a prediction model. Methods: This prospective cohort study administered a battery of cognitive and frailty screening instruments for 146 individuals (≥65 years old) scheduled for elective noncardiac surgery. Screening for CF was performed at least one day before surgery and tests for the presence of DNR were performed 7 days after surgery. The association between CF and DNR was investigated. Moreover, the study subjects were randomly divided into modeling group (70%) and validation group (30%). Univariate and multivariate Logistic regression were used to analyze the modeling group data and identify the independent risk factors for DNR. R software was used to construct DNR's nomogram model, and the model was verified. Results: In total, 138 individuals were eligible. 33 cases were diagnosed with DNR (23.9%). No significant difference in the number of patients with CF was observed between DNR and non-DNR groups (P >0.05). Multivariate analysis after adjusting relevant risk factors showed that only Judgment of Line Orientation (JLOT) test score had significant effect on incidence of DNR. After internal validation of the constructed DNR prediction model, the area under the curve (AUC) of the forecast probability for the modeling population (n=97) for DNR was 0.801, the AUC for the validation set (n=41) was 0.797. The calibration curve of both the modeling group and validation group indicates that the prediction model has good stability. Conclusion: Cognitive frailty is not an independent risk factor to predict DNR after noncardiac surgery in frail elders. Preoperative JLOT score is an independent risk factor for DNR in frail elderly individuals, and the prediction model has a good degree of discrimination and calibration, which can individually predict the risk probability of DNR in frail elderly.